Notes on Notes: Note-taking and Recordkeeping in Psychotherapy - Tudor, Keith; Gledhill, Kris (New Zealand Association of Psychotherapists (NZAP) Inc., 2022)
This article offers information and views about note-taking and record-keeping in the practice of psychotherapy in this country, in the context of the limited literature on the topic. It provides a brief review of what principal figures wrote about taking notes and making records, specifically Sigmund Freud and Eric Berne. It considers the purpose of making notes and keeping records, and presents key terms and conditions on the subject. Finally, it reviews relevant declarations and legislation regarding notes and records pertinent to the practice of psychotherapy in Aotearoa New Zealand.
Keywords: notes; note-taking; records; record-keeping; privacy